An efficient access control scheme in user hierarchy based on polynomial interpolation and hash function. (1st January 2014) - Das, Ashok Kumar; Goswami, Adrijit; Odelu, Vanga
The hierarchical cryptographic key assignment is used to assign cryptographic keys to a set of partially ordered security classes so that the user in a higher security class can derive the cryptographic secret keys of the other users in a lower security class. In this paper, we propose a practical solution for dynamic access problems in a user hierarchy, which uses the polynomial interpolation and hash function. When compared with other related recent existing access control schemes, in our scheme the computational complexity and the required storage space are significantly reduced. In addition, our scheme provides provable security. Furthermore, our scheme is easy to implement and therefore, it is more suitable for practical applications.